Cross sectoral Collaboration in Decision Support Systems for Critical Information Infrastructure Protection: An Innovative Approach - Prasetyo Adi Wibowo Putro; Satria Tegar Bimantara (Jurnal Sistem Informasi Bisnis, 2025)
The protection of Critical Information Infrastructure (CII) is increasingly challenged by evolving cyber threats and the growing interdependence of digital services, which require coordination beyond traditional, sector-siloed security approaches. This study proposes a Decision Support System (DSS) for CII protection that operationalizes cross-sector collaboration to generate dynamic security recommendations using a connectivity-first selection and a resource/governance similarity fallback when connected references are unavailable. Following the Knowledge Management Systems Development Life Cycle (KMSDLC), the DSS was designed and implemented based on structured interviews with stakeholders responsible for national digital services. The prototype was evaluated using the System Usability Scale (SUS) and achieved a mean score of 78.75 (“Good”), indicating strong user acceptance. The primary contribution is a reproducible, collaboration-enabled DSS mechanism that addresses limitations of static DSS models by supporting adaptive recommendations from structured cross-sector inputs. The study also provides practical implications for multi-stakeholder CIIP governance by clarifying how interdependence and similarity can be used to support auditable security-control recommendations. Future work will focus on outcome-based effectiveness evaluations (e.g., expert agreement and task completion time) and may optionally explore predictive analytics as a separate module; however, the current system remains rule-based and does not implement AI/ML components.